2004
DOI: 10.1149/1.1639162
|View full text |Cite
|
Sign up to set email alerts
|

Topotactic Two-Phase Reactions of Li[Ni[sub 1/2]Mn[sub 3/2]]O[sub 4] (P4[sub 3]32) in Nonaqueous Lithium Cells

Abstract: Li͓Ni 1/2 Mn 3/2 ͔O 4 was prepared by a two-step solid state reaction and characterized by X-ray diffraction ͑XRD͒, infrared ͑IR͒-Raman, and electron diffraction ͑ED͒. Li͓Ni 1/2 Mn 3/2 ͔O 4 having characteristic eight absorption bands in 400-800 cm Ϫ1 in IR spectrum, extra lines in XRD, and extra spots in ED was analyzed in terms of a superlattice structure. Analytical results on the structural data indicated that Li͓Ni 1/2 Mn 3/2 ͔O 4 ͑cubic: a ϭ 8.167 Å) was a superlattice structure based on a spinel framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
317
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(361 citation statements)
references
References 28 publications
37
317
1
1
Order By: Relevance
“…The calculated c/a ratio values are in good agreement with those reported in literature for highly-ordered lithiated spinel (space group P4 3 32). [20][21][22] The c/a values calculated for electrochemically-and chemically-obtained Li-rich phases are comparable and constant for the entire composition range, indicating that the Li insertion leads to a direct cubic-tetragonal phase transition without formation of intermediate phases, regardless of the lithiation method used.…”
Section: 28mentioning
confidence: 93%
See 1 more Smart Citation
“…The calculated c/a ratio values are in good agreement with those reported in literature for highly-ordered lithiated spinel (space group P4 3 32). [20][21][22] The c/a values calculated for electrochemically-and chemically-obtained Li-rich phases are comparable and constant for the entire composition range, indicating that the Li insertion leads to a direct cubic-tetragonal phase transition without formation of intermediate phases, regardless of the lithiation method used.…”
Section: 28mentioning
confidence: 93%
“…[19][20][21][22][23][24] The reasons of the different processes revealed by electrochemical analysis at low-potentials are currently under investigation and will be the subject of a later communication. From a practical point of view, it is clear that the overall capacity can be controlled by selecting the potential cutoff.…”
Section: 28mentioning
confidence: 99%
“…These two anodic signals have frequently been reported for Li-Ni-Mn spinels ͑particularly for LiNi 0.5 Mn 1.5 O 4 ). Recently, Ariyoshi et al 22 showed that the lithium deinsertion reaction at ca. 4.7 V involves two cubic/cubic two-phase reactions.…”
mentioning
confidence: 99%
“…One is the face-centered cubic (FCC) with the space group Fd3m and the other is the primitive simple cubic (SC) with the space group P4 3 32. [30][31][32][33] For the FCC structure, the unit cell consists of the Li ion-occupied tetrahedral 8a sites, Mn/Ni ion-occupied octahedral 16d sites, and O-occupied cubic close-packed 32e sites. The Mn/Ni ions in 16d sites are randomly distributed and thus the FCC spinel is often called the disordered structure.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%